Transformational Leadership Organizational Culture, Work Discipline, On Employee Performance at PT Hokkan Deltapack Industry - Dewi Hajrah; Endah Dewi Purnamasari; Mohammad Kurniawan (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine how the influence of transformational leadership, organizational culture and work discipline partially and simultaneouslyon employee performance at PT Hokkan Deltapack Industri. In this study collected through distributing questionnaires to 61 respondents. The data analysis technique used is multiple linear regression analysis models, with t tests and F tests. Meanwhile, what is used to see the extent of the accuracy and feasibility of the research variable instrument is used validity and reliability tests. The results of the t test analysis in this study indicate that partially transformational leadershiphas a significant effect (Sig.t 0.028 <0.05), organizational culture has a significant effect (Sig.t 0.033 <0.05) and work discipline has a significant effect on employee performance at PT Hokkan Deltapack Industri (Sig.t 0.000 <0.05). The results of the F test analysis and the coefficient of determination show that simultaneously transformational leadership, organizational culture and work discipline have a positive and significant influence on employee performance at PT Hokkan Deltapack Industri by 50.7 percent (Sig.F 0.000 <0.05). This shows that the better the transformational leadership, organizational culture and work discipline, the higher the performance produced by the employees of PT Hokkan Deltapack Industri